POLITICAL AND ECONOMIC FACTORS IN THE DECISION TO USE THE CHINESE VACCINE - Tonny Dian Effendi (Indonesian Association for International Relations, 2022)
This study discusses the factors that may influence the state to use the Chinese vaccines by examining the realism and liberal institution argument that the political value and institutions influence a state to cooperate with another state. This study examines the association between political (democracy) and economic (economic multilateral institution membership) factors and the state’s decision to use Chinese vaccines through regression analysis. This study found that: (1) states with a high level of democracy tend not to use vaccines from China and prefer to use other vaccines; (2) membership in multilateral economic cooperation under China’s leadership (BRI and AIIB) shows different tendencies in vaccine selection. This study shows that domestic politics and the nature of multilateral cooperation in an international institution influence state behavior. This study confirms that the vaccine is a global health issue, but political and economic factors appear to be associated with vaccine selection